Efficient Algorithmic and Architectural Optimization of QR-based Detector for V-BLAST - Fariborz Sobhanmanesh; Saeid Nooshabadi (Journal of Communications Software and Systems, 2005)
The use of multiple antennas at both transmitting and receiving sides of a rich scattering communication channelimproves the spectral efficiency and capacity of digitaltransmission systems compared with the single antennacommunication systems. However algorithmic complexity in the realization of the receiver is a major problem for itsimplementation in hardware. This paper investigates a nearoptimal algorithm for V-BLAST detection in MIMO wirelesscommunication systems based on the QR factorization technique, offering remarkable reduction in the hardware complexity. Specifically, we analyze some hardware implementation aspects of the selected algorithm through MATLAB simulations and demonstrate its robustness. This technique can be used in an efficient fixed point VLSI implementation of the algorithm. We also provide the VLSI architecture that implements the algorithm.